Quantitative susceptibility mapping of deep brain nuclei in 22q11.2 deletion syndrome - Muñoz, Nestor; García, Marisleydis; Cuiza, Analía; Tepper, Angeles; Vásquez, Javiera; Ramirez-Mahaluf, Juan Pablo; Barbagelata, Daniella; Aguirre, Juan; Maldonado, María Elisa; Ornstein, Claudia; Fritsch, Rosemarie; Repetto, Gabriela; et al. (Frontiers in Psychiatry, 2026)
Background22q11.2 Deletion Syndrome (22q11.2 DS) confers a high risk to dopamine-related disorders such as schizophrenia and Parkinson’s disease. These disorders have recently been associated with abnormal iron concentrations in deep brain nuclei. In this study we hypothesized that abnormal iron concentrations may also appear in deep brain nuclei of individuals with 22q11.2 DS.MethodsWe analyzed iron concentrations in four dopamine-related nuclei (caudate, putamen, substantia nigra, and globus pallidus) of 32 individuals, including adolescents and adults, carriers of the 22q11.2 DS and 49 healthy controls. For all individuals, we characterized iron concentrations in each region by quantifying R2* values and using a recently developed technique called Quantitative Susceptibility Mapping (QSM). We used linear mixed models to analyze potential differences between 22q11.2 DS individuals and our control group, considering brain region, age, sex, laterality, volume size, and framewise-displacement as fixed-effect covariates and individuals’ intercepts as random effects.ResultsAll individuals showed age-related increases in R2* values and susceptibility within dopaminergic nuclei (caudate, putamen, and substantia nigra). However, individuals with 22q11.2 DS showed a significantly lower rate of increase compared to healthy control group. This suggests that, over time, individuals with 22q11.2 deletion syndrome accumulate less iron in these nuclei than healthy controls.ConclusionsIndividuals with 22q11.2 DS present lower iron accumulation in dopaminergic areas, such as substantia nigra, caudate and putamen, relative to healthy controls. These findings suggest a possible association between a dopaminergic dysfunction and abnormal iron accumulation.